Principle of Technological Neutrality in Trade Facilitations: A Legal Perspective - Ika Riswanti Putranti (Universitas Ahmad Dahlan, 2022)
Introduction to The Problem: Electronic and digital trade systems encourage the use of information technology in their services. One of these is the single window. Technology is a neutral aspect of life that can pose significant problems in facilitating trade. These issues stem from the large-scale use of ICT that may cause inefficiency, uncertainty and barriers to trade through discrimination. Regulations related to technology continue to adapt to existing developments so as to ensure a sense of security and legal certainty in the use of technology. The concept of technology neutrality was created by the state to regulate the impartial or neutral use of technology.Purpose/Objective Study: This study aimed to describe the application of the Neutral Technology Principle in Trade Facilitation from a legal perspective and how the concept of neutral technology should be applied in international trade facilitation.Design/Methodology/Approach: The methodology used in this study is legal research with the normative judicial approach.Findings: The Principle of Technological Neutrality can guarantee the implementation of the principles of non-discrimination, efficiency, sustainability, and legal certainty in trade facilitation services.Paper Type: Research Article.